Photoinduced surface relief grating formation in amorphous As40S60-xSex thin films - Reinfelde, Mara; Loghina, Liudmila; Ivanova, Z. G.; Teteris, Janis; Gertners, Ugis; Šlang, Stanislav; Vlček, Miroslav (National Institute of Optoelectronics, 2016)
The studies of direct holographic recording of the surface relief gratings (SRG) on amorphous As40Se60-xSex (0 <= x <= 60) thin films are presented. The gratings were created by orthogonally +/- 45 degrees linearly polarized light beams of various wavelengths (lambda = 473 - 650 nm). The surface structure of the relief gratings was investigated by atomic force microscopy. The influence of laser beam wavelength and spatial frequency of the gratings (grating period Lambda) on the surface relief grating formation efficiency was examined.
Fotoindukovaná formace povrchových difrakčních mřížek v amorfních tenkých vrstvách systému As40S60-xSex
Keywords: Amorphous chalcogenide films; Holographic recording; Surface relief gratings; Amorfní chalkogenidové vrstvy; Holografický zápis; Difrakční mřížky